DEVELOPMENT OF ENGLISH LANGUAGE TEACHING USING INNOVATIVE TECHNOLOGIES - Ismatova Mekhribon (Galaxy International Interdisciplinary Research Journal, 2022)
This article will focus on the development of English language teaching using innovative technologies. The author, relying on scientific data, analyzed the problem based on the available literature and studied its specifics on the development of English language teaching using innovative technologies.